Construction method and application of ordered carbon layer coating structure on hard carbon surface

Through pre-carbonization, mechanical ball milling and high-temperature heat treatment, the crystallinity and orderliness of the carbon layer on the hard carbon surface and the microcrystalline structure are improved, and the problem of the electrochemical performance of hard carbon is affected by surface disorder is solved, and the performance of the negative electrode material of sodium ion battery is significantly improved.

CN119674021AInactive Publication Date: 2025-03-21BEIJING UNIV OF CHEM TECH

Patent Information

Application Number
CN202411893412.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The disorder of the carbon layer structure on the hard carbon surface has a significant impact on the electrochemical performance of the negative electrode materials of sodium ion battery, and it is difficult to effectively improve its crystallinity and microcrystalline structure through existing methods.

Method used

Through the steps of pre-carbonization treatment, mechanical ball milling treatment and high-temperature heat treatment, the surface microcrystalline structure of hard carbon materials is accurately controlled, and the crystallinity of the surface carbon layer and the order of the microcrystalline structure are improved.

Benefits of technology

The electrochemical performance of hard char as the negative electrode material of sodium ion battery is significantly improved, including first-time Coulomb efficiency, sodium storage capacity and cycling performance, enhancing the storage capacity of sodium ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674021A_ABST
    Figure CN119674021A_ABST
Patent Text Reader

Abstract

The invention provides a construction method and application of a hard carbon surface ordered carbon layer coating structure, and belongs to the technical field of sodium ion batteries, and the construction method comprises the following steps: pre-carbonizing an organic matter precursor in an inert atmosphere to obtain low-crystallinity hard carbon; then carrying out mechanical ball milling treatment on the obtained hard carbon under solid-phase and inert atmosphere conditions, and then carrying out purification treatment to obtain a carbon material of which the surface crystallinity is higher than that of the interior; and finally, carrying out high-temperature heat treatment on the obtained carbon material to obtain the hard carbon with an ordered carbon layer coating structure on the surface. By accurately controlling the surface microcrystalline structure of the hard carbon material, the electrochemical performance, including the first coulombic efficiency, the sodium storage capacity and the cycle performance, of the hard carbon as the sodium-ion battery negative electrode material is remarkably improved, and meanwhile, the constructed hard carbon material has higher surface carbon layer crystallinity and an optimized microcrystalline structure; the storage capacity of sodium ions is enhanced, and a foundation is laid for the development of sodium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a method for constructing a hard carbon surface ordered carbon layer coating structure and an application thereof. Background Art

[0002] With the continuous growth of global energy demand and the improvement of environmental protection awareness, finding efficient and environmentally friendly energy storage solutions has become an important direction of current scientific and technological research. Sodium-ion batteries are regarded as a powerful supplement to lithium-ion batteries due to their abundant sodium resources and low redox potential, and have huge market potential and application prospects. In the composition of sodium-ion batteries, the selection of negative electrode materials is crucial to their performance.

[0003] Hard carbon is recognized as the most suitable negative electrode material for sodium ion batteries due to its high stability and low sodium storage potential. The typical structural feature of hard carbon is that it contains a large number of closed-pore structures formed by disordered accumulation and bending of carbon microcrystals. This structure makes hard carbon exhibit unique electrochemical curves in the electrochemical process, including >0.1V (vs.Na + / Na) slope region and low potential platform region <0.1V. At present, the mainstream view on the electrochemical sodium storage mechanism of hard carbon is that Na + Adsorption on the surface defects of hard carbon contributes to the slope capacity; Na + The main plateau capacity is provided by diffusion from the carbon interlayers into the closed pores, thereby filling the closed pores.

[0004] However, the disorder of the carbon layer structure on the surface of hard carbon has a significant impact on its electrochemical performance. In particular, the surface microstructure (such as interlayer spacing and grain size) is a key factor affecting its first coulombic efficiency, sodium storage capacity and cycling performance. The ordered construction of the carbon layer structure on the surface of hard carbon and the improvement of crystallinity can reduce surface defects and transform exposed pores into closed pores, thereby improving the electrochemical performance of the material.

[0005] At present, the methods for designing an ordered carbon layer structure on the surface of hard carbon mainly include asphalt-based soft carbon coating and vapor deposition coating on the surface of small molecule compounds. Asphalt is a typical soft carbon precursor, and its crystallinity after pyrolysis and carbonization is significantly higher than that of hard carbon materials obtained from biomass, high molecular polymers or pre-oxidized asphalt under the same pyrolysis and carbonization conditions. Therefore, researchers have tried to coat the surface of hard carbon materials such as phenolic resin hard carbon (such as publication number CN111900400A), biomass hard carbon (such as publication number CN117963885A), and coal-based hard carbon (such as publication number CN118183739A) with asphalt, and then carbonize them to obtain hard carbon with a surface ordered carbon layer coating structure. In addition, there are also studies using small molecule compounds such as toluene and xylene (such as publication number CN116605864A) to pyrolyze and deposit carbon on the surface of hard carbon to achieve the purpose of surface coating or filling exposed pore structures. Although these methods have improved the orderliness of the carbon layer on the surface of hard carbon to a certain extent, they all belong to the path of surface composite carbon materials, and due to the chemical inertness of the carbon skeleton of hard carbon itself, it is difficult to effectively design its own structure under solid phase conditions.

[0006] Therefore, there is an urgent need for a simple, direct and efficient method to construct an ordered carbon layer coating structure on the surface of hard carbon to meet the application requirements of high-performance sodium-ion battery negative electrodes. Summary of the invention

[0007] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a method for constructing an ordered carbon layer coating structure on the surface of hard carbon and its application. By precisely controlling the surface microcrystalline structure of the hard carbon material, the electrochemical performance of the hard carbon as a negative electrode material for sodium ion batteries is significantly improved, including the first coulombic efficiency, sodium storage capacity and cycle performance. At the same time, the constructed hard carbon material has higher surface carbon layer crystallinity and optimized microcrystalline structure, which enhances the storage capacity of sodium ions and lays the foundation for the development of sodium ion batteries.

[0008] To achieve the above object, the present invention provides the following solutions:

[0009] A method for constructing a hard carbon surface ordered carbon layer coating structure comprises the following steps:

[0010] S1. Pre-carbonization treatment: pre-carbonizing the organic precursor under an inert atmosphere to obtain hard carbon with low crystallinity;

[0011] S2. Mechanical ball milling: The hard carbon obtained by pre-carbonization is subjected to mechanical ball milling in a solid phase and inert atmosphere, followed by purification to obtain a carbon material with a higher surface crystallinity than the internal carbon material;

[0012] S3. High temperature heat treatment: The carbon material obtained by mechanical ball milling is subjected to high temperature heat treatment to obtain hard carbon with a surface ordered carbon layer coating structure.

[0013] Preferably, in S1, the organic precursor is one or more of biomass material, high molecular polymer or pre-oxidized asphalt.

[0014] Preferably, in S1, the temperature of the pre-carbonization treatment is 600-800°C and the time is 1-4 hours, so as to obtain low-crystallinity hard carbon with a carbon content greater than 90 at.% and a carbon interlayer spacing greater than 0.380 nm.

[0015] Preferably, in S2, the solid phase condition of the mechanical ball milling treatment is direct ball milling of the hard carbon without adding liquid reagents; the inert atmosphere is one or more of argon, hydrogen and nitrogen.

[0016] Preferably, in S2, the rotation speed of the mechanical ball milling treatment is 300-2000 r / min, the mass ratio of grinding balls to hard carbon is 100:1-1000:1, and the time of the mechanical ball milling treatment is 3-12 h; the purification treatment includes acid washing, water washing and drying processes for the hard carbon after mechanical ball milling treatment.

[0017] Preferably, the surface crystallinity obtained in S2 is higher than that of the internal carbon material, and the (002) crystal plane interlayer spacing d of the surface carbon layer is 002 Smaller than the (002) interlayer spacing d inside the hard carbon material 002 , and the grain size La on the surface of the carbon material along the a-axis direction and the grain size Lc along the c-axis direction are both larger than La and Lc inside the carbon material.

[0018] Preferably, in S3, the high temperature heat treatment is performed at a temperature of 1200 to 1600° C. and for a time of 2 to 4 hours.

[0019] Preferably, in S3, after the high temperature heat treatment, a hard carbon having a surface ordered carbon layer coating structure is obtained, wherein the surface ordered carbon layer coating thickness of the hard carbon is 5 to 15 nm, and 0.365 nm < d 002 <0.380nm, 5nm<La<8nm, 4nm<Lc<7nm.

[0020] Preferably, the specific surface area of ​​the hard carbon is less than 5m 2 / g, the closed pore volume of the hard carbon is greater than 0.08cm 3 / g.

[0021] The present invention also provides hard carbon constructed by adopting the above-mentioned method for constructing an ordered carbon layer coating structure on the surface of hard carbon, which is used for preparing negative electrode materials of sodium ion batteries.

[0022] According to the specific embodiments provided by the present invention, the present invention discloses the following technical effects:

[0023] (1) The method of the present invention is simple and convenient, and the structure design is carried out directly from the hard carbon itself without the need for complicated coating or deposition process.

[0024] (2) The crystallite size, interlayer spacing and thickness of the surface-coated carbon layer structure in the technical solution of the present invention can be precisely controlled by mechanical ball milling process and high-temperature heat treatment temperature and time.

[0025] (3) The hard carbon obtained by the present invention has a surface carbon layer coating structure with high crystallinity, which is suitable as a negative electrode material for sodium ion batteries, exhibits high first coulombic efficiency, high reversible specific capacity and excellent cycle stability, and significantly improves the electrochemical performance of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0027] Figure 1 The present invention is a flow chart of a method for constructing an ordered carbon layer coating structure on a hard carbon surface.

[0028] Figure 2 This is a SEM image of the hard carbon prepared in Example 1 of the present invention.

[0029] Figure 3 This is the HRTEM image of the hard carbon prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and understandable, the present invention is described in detail below with reference to the accompanying drawings.

[0032] like Figure 1 As shown, the present invention provides a method for constructing an ordered carbon layer coating structure on a hard carbon surface, comprising the following steps:

[0033] S1. Pre-carbonization treatment: pre-carbonizing the organic precursor under an inert atmosphere to obtain hard carbon with low crystallinity;

[0034] S2. Mechanical ball milling: The hard carbon obtained by pre-carbonization is subjected to mechanical ball milling in a solid phase and inert atmosphere, followed by purification to obtain a carbon material with a higher surface crystallinity than the internal carbon material;

[0035] S3. High temperature heat treatment: The carbon material obtained by mechanical ball milling is subjected to high temperature heat treatment to obtain hard carbon with a surface ordered carbon layer coating structure.

[0036] Specifically, in S1, the organic precursor is one or more of a biomass material, a high molecular polymer or a pre-oxidized asphalt. The temperature of the pre-carbonization treatment is 600-800°C and the time is 1-4h, and a low-crystallinity hard carbon with a carbon content greater than 90at.% and a carbon interlayer spacing greater than 0.380nm is obtained. Among them, the organic precursor is used for a certain period of pre-carbonization treatment to obtain a low-crystallinity hard carbon with a carbon content greater than 90at.% and a carbon interlayer spacing greater than 0.380nm, which is used as a raw material for mechanical ball milling in step S2. The selection of pre-carbonization temperature and time is based on the microcrystalline structure of the raw material required for step S2: if the pre-carbonization temperature is too low or the time is too short, the obtained material will not be fully pyrolyzed, and the carbon content will be lower than 90at.%, and the large amount of retained heteroatoms will hinder the mechanochemical reaction of carbon and the orderly rearrangement of microcrystals during the ball milling process of step S2; if the pre-carbonization temperature is too high or the time is too long, the obtained material will have a high degree of crystallinity and the carbon interlayer spacing d 002 When the diameter is smaller than 0.380 nm, there are fewer active defects on the surface, and it is difficult to achieve the mechanochemical reaction and orderly rearrangement of the microcrystals during the ball milling process in step S2, thereby making it difficult to construct a structure in which the order of the surface microcrystal arrangement is higher than that of the interior.

[0037] Specifically, in S2, the solid phase condition of the mechanical ball milling treatment is to directly ball mill the hard carbon without adding liquid reagents; the inert atmosphere is one or more of argon, hydrogen, and nitrogen. The rotation speed of the mechanical ball milling treatment is 300-2000r / min, the mass ratio of grinding balls to hard carbon is 100:1-1000:1, and the time of the mechanical ball milling treatment is 3-12h; the purification treatment includes acid washing, water washing and drying of the hard carbon after mechanical ball milling.

[0038] In addition, the surface crystallinity obtained in S2 is higher than that of the internal carbon material, and the interlayer spacing d of the (002) crystal plane of the surface carbon layer is 002 Smaller than the (002) interlayer spacing d inside the hard carbon material 002 , and the grain size La on the surface of the carbon material along the a-axis direction and the grain size Lc along the c-axis direction are both larger than La and Lc inside the carbon material.

[0039] Step S2 is different from the method of adjusting the hard carbon microcrystalline structure by precursor type / molecular structure. It uses the low-crystallinity hard carbon obtained in step S1 as raw material for mechanical ball milling, and regulates the surface microcrystalline structure through mechanochemical reaction. Compared with the method of asphalt-based soft carbon coating or small molecule compound vapor deposition coating, this method is simpler and directly designs the structure from the hard carbon itself. The principle is that the high mechanical energy provided by ball milling directly acts on the C=C / CC bond of the hard carbon obtained in step S1, introducing a large number of active defects and free radicals, thereby inducing mechanochemical reactions, and promoting the development and orderly rearrangement of microcrystals under the continuous input of mechanical energy. In addition, the purpose of the purification treatment is to remove impurities introduced into the carbon material due to the wear of the grinding balls and the inner wall of the ball mill during the mechanical ball milling process.

[0040] The key to step S2 is that the mechanical ball milling conditions of the solid phase are necessary conditions for the mechanochemical reaction of carbon and the orderly rearrangement of microcrystals. The ball milling conditions of the solid phase and the inert atmosphere ensure that the carbon itself will not react with other non-carbon heteroatoms by producing mechanochemical reactions. The process parameters (rotation speed, ball-to-material ratio, ball milling time) are set to control the size of mechanical energy and the continuous input time, so that the mechanochemical reaction of carbon mainly occurs on the surface of hard carbon, limiting the effect of mechanical force on the microcrystalline structure inside hard carbon. During the mechanical ball milling process, the hard carbon particles are first broken, then agglomerated, reorganized and "cold welded": the carbon skeleton is mainly broken in the particle crushing stage, generating active defects and free radicals; the mechanochemical reaction of the surface carbon and the orderly rearrangement of microcrystals induced by active defects and free radicals mainly occur in the agglomeration and reorganization stage of the broken particles; and in the last continuous "cold welding" stage, the microcrystal mechanochemical reaction of the reorganized particles and the orderly rearrangement of the carbon layer gradually penetrate from the surface to the bulk phase. Under the conditions of lower rotation speed or ball-to-material ratio and shorter ball milling time, mechanical force will mainly cause particle crushing, defects and free radicals in hard carbon; on the contrary, higher rotation speed or ball-to-material ratio and longer ball milling time will cause continuous "cold welding" and orderly rearrangement of bulk carbon layer in hard carbon. Under the ball milling process provided in step S2, mechanical force induces a large number of active defects and free radicals on the surface of agglomerated and reorganized particles to undergo mechanochemical reactions, thereby regulating the surface carbon layer structure (crystal size, carbon layer spacing and thickness) to achieve an effect in which the surface crystallinity is higher than that of the interior. Therefore, the order of the surface carbon layer in the hard carbon after the subsequent step S3 heat treatment is much higher than that of the interior. In addition, after the mechanochemical reaction, a small amount of active defects and free radicals are still retained on the surface of the carbon material, which will further promote the orderly rearrangement of the surface crystallites during the subsequent step S3 heat treatment process, improve the surface crystallinity, and ultimately achieve the effect of surface orderly carbon layer coating.

[0041] Specifically, in S3, the temperature of the high temperature heat treatment is 1200-1600°C and the time is 2-4 hours. After the high temperature heat treatment, a hard carbon having a surface ordered carbon layer coating structure is obtained. The surface ordered carbon layer coating thickness of the hard carbon is 5-15nm, and 0.365nm<d 002 <0.380nm, 5nm<La<8nm, 4nm<Lc<7nm. The specific surface area of ​​the hard carbon is less than 5m 2 / g, the closed pore volume of the hard carbon is greater than 0.08cm 3 / g.

[0042] Among them, step S3 heat treats the carbon material with a higher surface crystallinity than the internal one obtained in step S2, so that defects and free radicals are reduced, and the crystallites further develop, grow, and rearrange under thermodynamic drive. Among them, the ability of orderly rearrangement of surface crystallites is better than that of the internal one, and the structure of the surface-coated ordered carbon layer is further controlled by the heat treatment temperature and time to match the performance requirements of the negative electrode of the sodium ion battery. If the heat treatment temperature is low or the treatment time is short, the orderly rearrangement of the surface carbon layer is insufficient, and the hard carbon is obtained with more exposed pore structures and surface defects. When used as the negative electrode of the sodium ion battery, the first coulomb efficiency and low potential platform capacity are not good; otherwise, the surface carbon layer spacing is too small and the crystallite size is large, and the interlayer diffusion of sodium ions cannot be achieved when used as the negative electrode of the sodium ion battery.

[0043] After testing, the hard carbon obtained by the present invention has a surface carbon layer coating structure with high crystallinity, and is suitable as a negative electrode material for sodium ion batteries. The sodium ion battery assembled with the hard carbon obtained by the present invention as the negative electrode active material has a high first coulombic efficiency, a high reversible specific capacity and excellent cycle stability, which further illustrates that the hard carbon obtained by the present invention can be applied to the negative electrode material of sodium ion batteries.

[0044] Based on the above content, the features and performances of the present invention are further described in detail below by listing specific implementation methods.

[0045] Embodiment 1

[0046] This embodiment provides a method for constructing an ordered carbon layer coating structure on a hard carbon surface, comprising the following steps:

[0047] S1. Pre-carbonization treatment: heat-treat the fruit shell at 700°C in a tubular furnace under nitrogen atmosphere for 2 hours to obtain hard carbon with low crystallinity;

[0048] S2. Mechanical ball milling: After pre-carbonization, the grinding balls and the obtained hard carbon are directly placed in a ball milling tank at a mass ratio of 400:1. The gas in the tank is replaced with argon gas and then mechanical ball milling is performed at a speed of 500 r / min for 5 h. After the ball milling is completed, the carbon material is taken out for acid washing, water washing and drying to obtain a carbon material with a higher surface crystallinity than the internal part;

[0049] S3. High-temperature heat treatment: The carbon material obtained by mechanical ball milling and purification treatment was heat treated at 1400°C in a tube furnace under argon atmosphere for 3 hours to obtain hard carbon with a surface ordered carbon layer coating structure. The SEM image of the hard carbon with a surface ordered carbon layer coating structure is as follows: Figure 2 As shown, through Figure 2 The characteristics of the aggregation degree, shape and size of the particles can be used to infer the changes in the carbon layer in different regions; the HRTEM image of hard carbon with an ordered carbon layer coating structure on the surface is shown in Figure 3 As shown, Figure 3 The coating thickness of the surface carbon layer is shown.

[0050] Embodiment 2

[0051] The construction method provided in this embodiment is basically the same as that provided in the first embodiment, except that the type of organic precursor and the mechanical ball milling process are changed in this embodiment. Specifically, the fruit shell in S1 is replaced with phenolic resin, and the ball-to-material ratio in S2 is adjusted to 800:1.

[0052] Embodiment 3

[0053] The construction method provided in this embodiment is basically the same as that provided in the first embodiment, except that the type of organic precursor and the mechanical ball milling process are changed in this embodiment. Specifically, the fruit shell in S1 is replaced with pre-oxidized asphalt, the mechanical ball milling atmosphere in S2 is adjusted to hydrogen, and the mechanical ball milling time is adjusted to 3 hours.

[0054] Embodiment 4

[0055] The construction method provided in this embodiment is basically the same as that provided in the first embodiment, except that the pre-carbonization conditions are changed in this embodiment, specifically, the pre-carbonization temperature in S1 is adjusted to 800°C.

[0056] Embodiment 5

[0057] The construction method provided in this embodiment is basically the same as that provided in the first embodiment, except that the mechanical ball milling process is changed in this embodiment, specifically, the mechanical ball milling speed in S2 is adjusted to 1500 r / min.

[0058] Embodiment 6

[0059] The construction method provided in this embodiment is basically the same as that provided in the first embodiment, except that the mechanical ball milling process is changed in this embodiment, specifically, the mechanical ball milling time in S2 is adjusted to 10 h.

[0060] Embodiment 7

[0061] The construction method provided in this embodiment is basically the same as that provided in the first embodiment, except that the high-temperature heat treatment conditions are changed in this embodiment, specifically, the high-temperature heat treatment temperature in S3 is adjusted to 1600°C.

[0062] Comparative Example 1

[0063] The construction method provided in this comparative example is basically the same as that provided in Example 1, except that the pre-carbonization treatment in this comparative example is insufficient, specifically, the pre-carbonization treatment temperature in S1 is adjusted to 500°C.

[0064] Comparative Example 2

[0065] The construction method provided in this comparative example is basically the same as that provided in Example 1, except that the pre-carbonization treatment in this comparative example is excessive, specifically, the pre-carbonization treatment time in S1 is adjusted to 6 hours.

[0066] Comparative Example 3

[0067] The construction method provided in this comparative example is basically the same as that in Example 1, except that the mechanical ball milling condition in this comparative example is non-solid phase. Specifically, the solid phase mechanical ball milling treatment condition in S2 is adjusted to a liquid phase condition of adding 5 mL of deionized water.

[0068] Comparative Example 4

[0069] The construction method provided in this comparative example is basically the same as that provided in Example 1, except that the mechanical ball milling atmosphere in this comparative example is not protected by an inert gas. Specifically, the solid phase mechanical ball milling treatment condition in S2 is adjusted so that the atmosphere in the tank is air.

[0070] Comparative Example 5

[0071] The construction method provided in this comparative example is basically the same as that provided in Example 1, except that the mechanical ball milling mechanical force in this comparative example is insufficient. Specifically, the rotation speed of the mechanical ball milling treatment in S2 is adjusted to 200 r / min.

[0072] Comparative Example 6

[0073] The construction method provided in this comparative example is basically the same as that provided in Example 1, except that the mechanical energy input of the mechanical ball milling in this comparative example is excessive, specifically, the mechanical ball milling treatment time in S2 is adjusted to 15 h.

[0074] Comparative Example 7

[0075] The construction method provided in this comparative example is basically the same as that provided in Example 1, except that the high-temperature heat treatment in this comparative example is insufficient, specifically, the high-temperature heat treatment time in S3 is adjusted to 1 hour.

[0076] Comparative Example 8

[0077] The construction method provided in this comparative example is basically the same as that provided in Example 1, except that the high-temperature heat treatment in this comparative example is excessive, specifically, the high-temperature heat treatment temperature in S3 is adjusted to 1800°C.

[0078] Comparative Example 9

[0079] This comparative example provides a method for direct precursor carbonization, which is in contrast to the method for constructing an ordered carbon layer coating structure on the surface of hard carbon in the present invention. This comparative example is basically the same as Example 1, except that the mechanical ball milling step of S2 is not taken.

[0080] The hard carbon obtained in the above examples and comparative examples was structurally characterized, wherein the surface ordered carbon layer coating thickness was obtained from the width of the surface ordered oriented carbon layer in the HRTEM image, and the results are shown in Table 1:

[0081] Table 1 Ordered carbon layer structure data of hard carbon surface coating in different embodiments and comparative examples

[0082]

[0083]

[0084] In order to further verify that the hard carbon obtained by the method for constructing a hard carbon surface ordered carbon layer coating structure described above can be used to prepare the negative electrode material of sodium ion battery, the hard carbon materials obtained in the above embodiment and comparative example were subjected to electrochemical sodium storage test, and the results are shown in Table 2:

[0085] Table 2 Electrochemical sodium storage test data

[0086]

[0087]

[0088] Therefore, by comparing the relevant data in Table 1 and Table 2, it can be seen that the above-mentioned method for constructing an ordered carbon layer coating structure on the surface of hard carbon and its application, by precisely controlling the surface microcrystalline structure of the hard carbon material, significantly improves the electrochemical performance of hard carbon as a negative electrode material for sodium ion batteries, including the first coulombic efficiency, sodium storage capacity and cycle stability. At the same time, the constructed hard carbon material has higher surface carbon layer crystallinity and optimized microcrystalline structure, which enhances the storage capacity of sodium ions and lays the foundation for the development of sodium ion batteries.

[0089] The principles and implementation methods of the present invention are described in this article using specific examples. The description of the above embodiments is only used to help understand the method and core idea of ​​the present invention. At the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as limiting the present invention.

Claims

1. A method for constructing an ordered carbon layer coating structure on a hard carbon surface, characterized in that: The following steps are involved: S1. Pre-carbonization treatment: pre-carbonizing the organic precursor under an inert atmosphere to obtain hard carbon with low crystallinity; S2. Mechanical ball milling: The hard carbon obtained by pre-carbonization is subjected to mechanical ball milling in a solid phase and inert atmosphere, followed by purification to obtain a carbon material with a higher surface crystallinity than the internal carbon material; S3. High temperature heat treatment: The carbon material obtained by mechanical ball milling is subjected to high temperature heat treatment to obtain hard carbon with a surface ordered carbon layer coating structure.

2. The method for constructing a hard carbon surface ordered carbon layer coating structure according to claim 1, characterized in that: In S1, the organic precursor is one or more of biomass material, high molecular polymer or pre-oxidized asphalt.

3. The method for constructing a hard carbon surface ordered carbon layer coating structure according to claim 2, characterized in that: In S1, the temperature of the pre-carbonization treatment is 600-800°C and the time is 1-4 hours, so as to obtain low-crystallinity hard carbon with a carbon content greater than 90 at.% and a carbon interlayer spacing greater than 0.380 nm.

4. The method for constructing a hard carbon surface ordered carbon layer coating structure according to claim 1, characterized in that: In S2, the solid phase condition of the mechanical ball milling treatment is direct ball milling of the hard carbon without adding liquid reagents; the inert atmosphere is one or more of argon, hydrogen, and nitrogen.

5. The method for constructing a hard carbon surface ordered carbon layer coating structure according to claim 4, characterized in that: In S2, the rotation speed of the mechanical ball milling treatment is 300-2000 r / min, the mass ratio of grinding balls to hard carbon is 100:1-1000:1, and the time of the mechanical ball milling treatment is 3-12 hours; the purification treatment includes acid washing, water washing and drying processes for the hard carbon after mechanical ball milling treatment.

6. The method for constructing a hard carbon surface ordered carbon layer coating structure according to claim 5, characterized in that: The surface crystallinity obtained in S2 is higher than that of the internal carbon material, and the interlayer spacing d of the (002) crystal plane of the surface carbon layer is 002 Smaller than the (002) interlayer spacing d inside the hard carbon material 002 , and the grain size La on the surface of the carbon material along the a-axis direction and the grain size Lc along the c-axis direction are both larger than La and Lc inside the carbon material.

7. The method for constructing a hard carbon surface ordered carbon layer coating structure according to claim 1, characterized in that: In S3, the high temperature heat treatment is performed at a temperature of 1200 to 1600°C and for a time of 2 to 4 hours.

8. The method for constructing a hard carbon surface ordered carbon layer coating structure according to claim 7, characterized in that: In S3, after the high temperature heat treatment, hard carbon with a surface ordered carbon layer coating structure is obtained, wherein the surface ordered carbon layer coating thickness of the hard carbon is 5 to 15 nm, and 0.365 nm < d 002 <0.380nm, 5nm<La<8nm, 4nm<Lc<7nm.

9. The method for constructing a hard carbon surface ordered carbon layer coating structure according to claim 8, characterized in that: The specific surface area of ​​the hard carbon is less than 5m 2 / g, the closed pore volume of the hard carbon is greater than 0.08cm 3 / g.

10. The hard carbon obtained by the method for constructing a hard carbon surface ordered carbon layer coating structure according to any one of claims 1 to 9, characterized in that: The hard carbon is used for preparing the negative electrode material of the sodium ion battery.

Citation Information

Patent Citations

  • Preparation method of soft carbon coated hard carbon negative electrode material for lithium ion battery

    CN111900400A

  • Preparation method of phenolic resin-based sodium ion battery hard carbon negative electrode material

    CN116605864A

  • High-rate biomass-based hard carbon negative electrode material and preparation method thereof

    CN117963885A

  • Coal-based hard carbon negative electrode material, preparation method thereof and sodium ion battery

    CN118183739A

  • Biomass hard carbon negative electrode material for sodium ion battery as well as preparation method and application of biomass hard carbon negative electrode material

    CN113381016A

Cited By

  • Biomass hard carbon material with low pH value, preparation method and application thereof, negative pole piece for sodium ion battery, and sodium ion battery

    CN120221649A

  • Medical composite material for cooperatively regulating cholesterol and oxidative stress

    CN122005912A